Idea of Rural Development: A Study of Planning in Management of Rural Development in Assam - Barua, Dr Bulbuli (Innovative Research Thoughts, 2017)
Rural Development occupies a vital place in the planning and policy formulation of developing counties like India. But today rural development is all comprehensive. There is hardly any aspect of social life which is left out from the preview of rural development. It is not only concerned with socio-economic, political, cultural and administrative aspects of society but aims at improvement of the quality of life of all sections of rural people. So it is all inclusive. In view of expanding nature of rural development, management becomes an urgent necessity. The present paper will focus the idea of rural development with a study on the planning in management of rural development in Assam.